2021
DOI: 10.1038/s41588-021-00893-0
|View full text |Cite
|
Sign up to set email alerts
|

p53 convergently activates Dux/DUX4 in embryonic stem cells and in facioscapulohumeral muscular dystrophy cell models

Abstract: ertilization and early embryogenesis involve the transition from specialized unipotent gametes to totipotent embryos. After fertilization, mammalian embryos rely on maternally deposited RNA but subsequently initiate ZGA during which embryonic transcription begins 1 . Diverse mechanisms control the timing of ZGA, such as controlling RNA polymerase activity, the nuclear/ cytoplasmic ratio, or translation of critical ZGA transcription factors (TFs) in Caenorhabditis elegans, Drosophila melanogaster or Danio rerio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 68 publications
9
84
0
Order By: Relevance
“…Studies on the role of p53 in ground-state 2iESCs produced contradictory results that mirror those reported for naïve ESCs. Two studies in mouse 2iESCs revealed that DNA damage induced either by aphidicolin inhibition of DNA polymerase-alpha or doxorubicin inhibition of topoisomerase II activates genes characteristic of zygotic gene expression in mouse 2-cell to 4-cell embryos [161,162]. Both studies concluded that the mechanism driving this expression is mediated by an ATR and CHK1 response to double-strand DNA breaks.…”
Section: Dna Damage Response In Ground-state 2iescsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the role of p53 in ground-state 2iESCs produced contradictory results that mirror those reported for naïve ESCs. Two studies in mouse 2iESCs revealed that DNA damage induced either by aphidicolin inhibition of DNA polymerase-alpha or doxorubicin inhibition of topoisomerase II activates genes characteristic of zygotic gene expression in mouse 2-cell to 4-cell embryos [161,162]. Both studies concluded that the mechanism driving this expression is mediated by an ATR and CHK1 response to double-strand DNA breaks.…”
Section: Dna Damage Response In Ground-state 2iescsmentioning
confidence: 99%
“…Both studies concluded that the mechanism driving this expression is mediated by an ATR and CHK1 response to double-strand DNA breaks. However, one study concluded that activation required p53 expression [162], whereas the other study concluded that it did not [161]. Critical experiments in which p53+/+ and p53-/-2iESCs were compared were carried in both studies, but with opposite results.…”
Section: Dna Damage Response In Ground-state 2iescsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the role of p53 in ground-state 2iESCs produced contradictory results that mirror those reported for naïve ESCs. Two studies in mouse 2iESCs revealed that DNA damage induced either by aphidicolin inhibition of DNA polymerase-α or doxorubicin inhibition of topoisomerase II activates genes characteristic of zygotic gene expression in mouse 2-cell to 4-cell embryos [161,162]. Both studies concluded that the mechanism driving this expression is mediated by an ATR and CHK1 response to double-strand DNA breaks.…”
Section: Dna Damage Response In Ground-state 2iescsmentioning
confidence: 99%
“…Both studies concluded that the mechanism driving this expression is mediated by an ATR and CHK1 response to double-strand DNA breaks. However, one study concluded that activation required p53 expression [162],…”
Section: Dna Damage Response In Ground-state 2iescsmentioning
confidence: 99%